Anaesthesiology and intensive care Hemodynamic consequences of different ventilation methods used in lung surgery - Misiołek, Hanna; Budziński, Dariusz; Karpe, Jacek; Knapik, Piotr; Czyżewski, Damian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Anesthesia techniques used in thoracic surgery are completely different from those used in general surgery, because thoracic surgery requires both effective ventilation and immobilization of the operating area. One lung ventilation (OLV) remains the standard ventilation method used during thoracic surgery procedures. The most frequent position of the patient during thoracotomy is the lateral decubitus position opposite to the operated side. The abovementioned conditions lead to several respiratory, hemodynamic, and oxygenation disturbances. However, high-frequency jet ventilation (HFJV) may be used as an alternative way of ventilation during lung resection. Both ventilation methods provide full or partial immobilization of the operative field, but they result in different hemodynamic effects. Comparing the cardiovascular parameters during OLV and HFJV we can definitely say that HFJV provides better oxygenation and ventilation in comparison to OLV, while maintaining hemodynamic stability.